Music therapy for premature and newborn infants - Nöcker-Ribaupierre, Monika (Barcelona Publishers, 2019)
This comprehensive international collection of writings on music therapy for premature and newborn infants was first published in 2003, and appears here in a second updated edition. The book chapters are based on a wide interdisciplinary range covering writings on medicine, infant and bonding research, developmental psychology, psychoanalysis, as well as music therapy in its different approaches.
Keywords: Music therapy for children